荒诞派戏剧《椅子》与其昆剧改编比较研究. - 秦璇 (Foreign Literature Studies, 2025)
Eugène Ionesco's The Chairs is a classic masterpiece of absurdist theatre, while Kunqu Opera, revered as the "ancestor of all operas" in China, is a household treasure as part of the nation's cultural heritage. The eponymous Kunqu Opera The Chairs, adapted by playwright Yu Xiating, is endowed with new vitality based on the essence of musical tones of Kunqu's "water-polished melody," serving as an outstanding model of the dialogue and fusion between Chinese and Western theatre. The differences between the two versions of The Chairs, which lie in the three core dimensions of creative context, cross-cultural philosophical dialogue, and artistic adaptation, reveal the underlying divergences in Chinese and Western philosophical and artistic conceptions. The absurdist play The Chairs employs concise and direct language, a loose and free structure, and abstract stage performance to directly confront the spiritual predicament of "individual loneliness" and "existential nihility" of humanity in post-war Western society; in contrast, the Kunqu Opera The Chairs, with its elegant libretto rhythm, rigorous narrative structure, and refined stage aesthetics, transforms Western existential interrogation into the expression of local wisdom that integrates Confucian ideals of "active worldly engagement and striving for advancement" with Taoist notions of "transcendent detachment and adherence to constancy." This cross-cultural transcoding mediated by traditional Chinese philosophy not only achieves the contemporary revitalization of traditional Kunqu Opera but also builds a platform for equal exchange between Chinese and Western theatre, providing an exemplar of both theoretical value and practical significance for the cross-cultural innovation and development of traditional Kunqu Opera and other Chinese opera genres.